2019
DOI: 10.1111/cns.13192
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of dorsal root ganglion stimulation for pain relief in painful diabetic polyneuropathy is not dependent on GABA release in the dorsal horn of the spinal cord

Abstract: AimsIt is hypothesized that dorsal root ganglion stimulation (DRGS), sharing some of the mechanisms of traditional spinal cord stimulation (SCS) of the dorsal columns, induces γ‐aminobutyric acid (GABA) release from interneurons in the spinal dorsal horn.MethodsWe used quantitative immunohistochemical analysis in order to investigate the effect of DRGS on intensity of intracellular GABA‐staining levels in the L4‐L6 spinal dorsal horn of painful diabetic polyneuropathy (PDPN) animals. To establish the maximal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 55 publications
(95 reference statements)
2
26
0
1
Order By: Relevance
“…Previous animal studies of SCS demonstrated increased levels of γ‐amino butyric acid (GABA), an inhibitory neurotransmitter, in the spinal cord (71), and increased paw withdrawal thresholds in animals that responded to SCS (72) predominantly driven through the GABA B receptor (73, 74). However, a recent study in rats concluded that DRGS does not cause GABA release in the dorsal horn (75), indicating DRGS may provide pain relief through other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous animal studies of SCS demonstrated increased levels of γ‐amino butyric acid (GABA), an inhibitory neurotransmitter, in the spinal cord (71), and increased paw withdrawal thresholds in animals that responded to SCS (72) predominantly driven through the GABA B receptor (73, 74). However, a recent study in rats concluded that DRGS does not cause GABA release in the dorsal horn (75), indicating DRGS may provide pain relief through other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Koetsier and colleagues suggested that instead of driving GABAergic inhibition in the dorsal horn, DRGS may provide pain relief by inducing GABAergic inhibition through GABA signaling within the DRG (75). Du and colleagues concluded that in rats, activating small‐, medium‐, or large‐diameter DRG neurons can induce GABA release in the DRG, and that nearly all small‐diameter DRG neurons (putative nociceptors) can respond to GABA (76).…”
Section: Discussionmentioning
confidence: 99%
“…However, administration of GABA and glycine antagonists do not block inhibition by very low frequency (<20 Hz) stimulation (131, 132). A recent study demonstrated that DRG‐S does not induce GABA release in the DH (141). Thus, DRG‐S, especially at very low frequencies, is likely to be less dependent on GABAergic mechanisms.…”
Section: T12 Drg‐s For Axial Lbp: Integrating the Evidencementioning
confidence: 99%
“…Although a recent computational study indeed suggested that DRGS may inhibit nociception by activating pain-gating mechanisms in the dorsal horn through repeated activation of large myelinated (Aβ) afferents, 31 another study found that the pain-relieving effect of DRGS is not likely to be dependent on GABA release in the spinal dorsal horn at the L4-L6 lumbar level. 47 Some experimental studies suggest that, instead, DRGS suppresses excitability of neurons with predominantly slow-conducting nociceptive fibers (C fibers). 44 , 48 Because of the unique pseudounipolar design of DRG neurons, the DRG is likely to act as an impediment or low-pass filter to electrical impulses traveling from the peripheral nociceptor to the spinal cord in response to electrical stimulation (Fig.…”
Section: New Stimulation Location: the Dorsal Root Ganglionmentioning
confidence: 99%